Penyuluhan dan Pendampingan Penulisan Karya Tulis Kewirausahaan untuk Membangun Generasi Muda Berprestasi - Roudlotul Badi'ah; Achmad Farid Dedyansyah; Maria Arista Ulfa; Ahmad Syauqi; Evi Maya Odelia (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
This community service activity is focused on the younger generation to foster writing skills and develop creativity through training in writing scientific papers. The training methods used include counseling and a participatory approach, with a mentoring duration of one year. The counseling focuses on guidance on techniques for writing entrepreneurial papers, as well as assistance involving demonstrations, writing practice, and public speaking for presentations. The material presented includes motivation and generating ideas, tips, and tricks for preparing business plans and the Business Model Canvas (BMC). The target group consists of three teams, namely the team from MAN 1 Lamongan, Sebelas Maret University, and the Bogor Agricultural Institute. The results of this mentoring show that the three teams achieved several national achievements in making entrepreneurial proposals, developing presentation skills, and increasing competitive courage. Therefore, assistance in writing scientific papers is helpful for the younger generation in increasing creativity and achievement through writing and public speaking. The implications of this community service activity are improving the ability to write entrepreneurial papers, developing presentation skills, achieving motivation for pupils and students, contributing to entrepreneurship development among the younger generation, and positively impacting economic and social development.